Do pathogens from corneal scraping show their true colours better in bactec bottles? - Logeswary K,; Hazlita Mohd Isa,; Wan Haslina Wan Abdul Halim,; Then, KY; Aida Zairani Mohd. Zahidin, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Identification of causative organisms of clinically suspected microbial keratitis is very important so that appropriate targeted antimicrobial treatment can be offered to patients. The current routine method of corneal scraping specimens on to multiple agar culture plates for microbiological study is not really providing encouraging result. Our trial of modified technique of using BACTEC broth for three clinically suspected microbial keratitis cases worked 100% to identify the causative organisms in cases of microbial keratitis.